Analysis of the Psychological Impact of the Conductor "Konjak" on Adolescent in Kupang City - Daik, Irene Elvira; Noach, Yuvine Marlene Cicilia; Sheldena, Devi Novita (KnE Social Sciences, 2024)
This research is motivated by the phenomenon of underage conductor workers aged 12–15 years. Early adolescents still require the development of various aspects in preparation for entering adulthood. Early adolescents are not ready to enter the world of work. This study aims to analyze the psychological impact of early adolescent conductor workers physically, cognitively, emotionally, and socially in the Oebufu sub-district, Oebobo sub-district, and Kupang city. The research method used is descriptive-qualitative. The research subjects were 10 young conductors aged 12–15 years. Data collection techniques include non-participatory observation and semi-structured interviews. The data obtained was then analyzed through three stages: data reduction, data display, and conclusion. The results showed that working in early adolescence had a negative impact on the subjects’ development in mental, physical, cognitive, and social aspects. Subjects are prone to experiencing conflict at work because they are emotionally unstable and do not have the skills to socialize with customers of various ages. Subjects are also prone to verbal and non-verbal aggressive treatment from older co-workers (drivers). Subjects are often depressed because the wages received are erratic. Subjects do not eat regularly and do not have time to exercise because they have to work from morning to night, even though they are in a growth period that can be maximized through exercise and consuming nutritious food on time. Busy work also causes subjects to drop out of school, so they lose the opportunity to practice their cognitive potential through education according to the stages of their intellectual change. Socially, subjects are easily influenced by the bad habits of smoking and consuming alcohol due to association with more mature co-drivers. Keywords: conductor, Konjak, adolescent, psychological impact